RESISTENSI Mycobacterium Tuberculosis TERHADAP OBAT ANTI TUBERKULOSIS - A. Nikmawati; Windarwati Windarwati; Hardjoeno Hardjoeno (Indonesian Association of Clinical Pathologist and Medical laboratory, 2005)
Patients infected with resistant Mycobacterium tuberculosis strain will be very difficult to cure by standard treatment. To evaluatethe drug resistance of Mycobacterium tuberculosis. A Cross sectional study was performed from January until July 2005. Samples wereobtained from sputum of the suspect tuberculosis. All samples were cultured in Lowenstein-Jensen Media and followed by sensitivity testaccording to resistance ratio method. Of 236 samples, there were 30% positive cultures. The percentage of mono-resistance to Isoniazidwas 70%, to Rifampicin 64.3%, to Ethambutol 62.8% and Streptomycin 64.3%. The percentage of Multi Drug Resistant Tuberculosis(MDR-TB) was 20–40% and the percentage of poly-resistant (Ethambutol and Streptomycin) was 47.1%. The percentage of suspecttuberculosis with positive culture was 30%. There were also found high percentage of mono-resistant, poly-resistant and MDR-TB.